Zika Virus: Diagnostics for an Emerging Pandemic Threat - Waggoner, Jesse J.; Pinsky, Benjamin A. (Journal of clinical microbiology, 2016)
Zika virus (ZIKV) is an Aedes mosquito-borne flavivirus that emerged in Brazil in 2015 and then rapidly spread throughout the tropical and subtropical Americas. Based on clinical criteria alone, ZIKV cannot be reliably distinguished from infections with other pathogens that cause an undifferentiated systemic febrile illness, including infections with two common arboviruses, dengue virus and chikungunya virus. This minireview details the methods that are available to diagnose ZIKV infection.